2015
DOI: 10.1002/jcla.21869
|View full text |Cite
|
Sign up to set email alerts
|

Fasting Lipoprotein Lipase Protein Levels Can Predict a Postmeal Increment of Triglyceride Levels in Fasting Normohypertriglyceridemic Subjects

Abstract: Fasting LPL levels may be useful to predict postprandial TG increment in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Tsuzaki et al reported supportive ndings. They found that fasting LPL mass levels may be useful as a predictor of increased postprandial triglycerides and that fasting LPL mass is a simple and easy-to-use marker in clinical practice [16]. On the other hand, no signi cant increase in LPL activity was found during chylomicron and VLDL overload after different kinds of food intake [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tsuzaki et al reported supportive ndings. They found that fasting LPL mass levels may be useful as a predictor of increased postprandial triglycerides and that fasting LPL mass is a simple and easy-to-use marker in clinical practice [16]. On the other hand, no signi cant increase in LPL activity was found during chylomicron and VLDL overload after different kinds of food intake [17].…”
Section: Discussionmentioning
confidence: 99%
“…Missense mutations that interfere with LPL-GPIHBP1 interactions profoundly impair intravascular triglyceride processing, resulting in severe hypertriglyceridemia [14,15]. Fasting LPL mass levels may be useful as a predictor of postprandial triglyceride increases in fasting normotriglyceridemic subjects, and fasting LPL mass is a simple easy-to-use marker that can be applied in clinical practice [16]. On the other hand, no signi cant increase in LPL activity was found during chylomicron and very low-density lipoprotein (VLDL) overload after different kinds of food intake [17].…”
Section: Introductionmentioning
confidence: 99%
“…Missense mutations that interfere with LPL–GPIHBP1 interactions profoundly impair intravascular TG processing, resulting in severe hypertriglyceridemia [ 14 , 15 ]. As it is a simple and easy-to-use marker that can be applied in clinical practice, fasting LPL mass may prove useful in predicting postprandial TG elevation in fasting individuals with normal TG levels [ 16 ]. Alternatively, no significant increase in LPL activity was found during chylomicron, and very low-density lipoprotein (VLDL) overload after eating different kinds of food [ 17 ].…”
Section: Introductionmentioning
confidence: 99%